PERAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN EFEKTIVITAS DAN EFISIENSI PENGAMBILAN KEPUTUSAN DI LINGKUNGAN ORGANISASI MODERN - Luna Syahfina; Muhammad Irwan Padli Nasution (CV. Barokah Publsiher, 2025)
This study aims to analyze the role of Management Information Systems (MIS) in improving the effectiveness and efficiency of decision-making within modern organizational environments. Using a descriptive qualitative approach supported by an extensive literature review of academic journals, policy documents, and previous empirical studies, this research offers a comprehensive evaluation of how MIS influences managerial processes. The findings reveal that the implementation of MIS significantly enhances decision-making effectiveness by ensuring the availability of accurate, relevant, and timely information needed at various organizational levels. MIS also facilitates structured data processing, analytical reporting, and real-time monitoring, which strengthen strategic decision-making and reduce uncertainty. In addition, MIS contributes to improving decision-making efficiency by accelerating the flow of information, minimizing administrative errors, and reducing operational costs through the automation of routine tasks and standardized workflows. Moreover, MIS supports collaboration and communication by enabling integrated data access across departments, thereby reducing information silos and improving organizational responsiveness. In conclusion, MIS plays an essential and transformative role in shaping a fast, accurate, data-driven, and adaptive decision-making system, particularly for modern organizations operating in a dynamic and competitive digital era.